Sleep-deprived electroencephalography, a forgotten investigation in psychiatry; a case series. (January 2023) - Najand, Babak; Christensen, Andrew; Martin, Michael; Spelman, Mark
Objectives: Many patients with psychiatric disorders may have epileptic disorders; however, clinical diagnosis without imaging investigation may result in misdiagnosis and thus resistance to treatment. We investigated electroencephalography (EEG) abnormalities in the patients with psychiatric disorders referred to us with treatment resistance. Methods: In this case series study, nine patients with mood and psychotic symptoms who were referred to us at Belmont Private Hospital, Australia, from August 2018 to July 2020, were evaluated. Results: Complete examination showed the presence of undiagnosed temporal lobe epilepsy. Notably, the seizure symptoms had been assumed as part of other psychiatric co-morbidities. Conclusions: This study suggests the necessity of paying attention to the biological etiologies of mental illnesses in the initial assessments in psychiatric and neurological practice. Performing electroencephalogram and treating such patients with mood stabilizers, which have antiepileptic properties, can change the course of the mental illness decisively.